Impact of the application of lean manufacturing in sausage production line equipment in the food manufacturing industry in Metropolitan Lima - Quiroz Melgarejo, Brayan Alexander (2023)
The present investigation was carried out in a food manufacturing company in Metropolitan Lima, specifically in the Meats and sausages industry category. The investigation is focused on three stuffing machines within the sausage production line. The problem is the low overall efficiency expressed by the OEE indicator, which initially was an average of 60.479% for the three stuffing machines, compared to the world-class OEE, which according to Nakajima, is 85%. In order to improve the OEE indicator, the company implemented the use of Shoplogix software and applied lean manufacturing methodologies in its sausage production lines. Due to this, the main objective was to describe the impact generated by implementing lean manufacturing methodologies in the OEE. For this, information was collected from primary sources for four weeks, and historical data of four years was used on the OEE indicator and the main problems detected in the stuffing machines. Finally, normality and Student's t-tests were performed, showing that implementing lean manufacturing methodologies positively impacted the OEE, increasing an average of 5.9583%. It was also shown that the software-generated implementation significantly changed the OEE's data collection and calculation. This improvement is translated into more than 2 million dollars in savings from its implementation until 2021.